A Closure for Lee Wave Drag on the Large-Scale Ocean Circulation - Eden, Carsten; Olbers, Dirk; Eriksen, Thomas (Journal of Physical Oceanography, 2021)
A new, energetically, and dynamically consistent closure for the lee wave drag on the large-scale circulation is developed and tested in idealized and realistic ocean model simulations. The closure is based on the radiative transfer equation for internal gravity waves, integrated over wavenumber space, and consists of two lee wave energy compartments for up- and downward propagating waves, which can be cointegrated in an ocean model. Mean parameters for vertical propagation, mean–flow interaction, and the vertical wave momentum flux are calculated assuming that the lee waves stay close to the spectral shape given by linear theory of their generation. Idealized model simulations demonstrate how lee waves are generated and interact with the mean flow and contribute to mixing, and document parameter sensitivities. A realistic eddy-permitting global model at 1/10° resolution coupled to the new closure yields a globally integrated energy flux of 0.27 TW into the lee wave field. The bottom lee wave stress on the mean flow can be locally as large as the surface wind stress and can reach into the surface layer. The interior energy transfers by the stress are directed from the mean flow to the waves, but this often reverses, for example, in the Southern Ocean in case of shear reversal close to the bottom. The global integral of the interior energy transfers from mean flow to waves is 0.14 TW, while 0.04 TW is driving the mean flow, but this share depends on parameter choices for nonlinear effects.